Aliskiren Administration during Early Postnatal Life Sex-Specifically Alleviates Hypertension Programmed by Maternal High Fructose Consumption - Hsu, Chien-Ning; Wu, Kay L. H.; Lee, Wei-Chia; Leu, Steve; Chan, Julie Y. H.; Tain, You-Lin (Frontiers in Physiology, 2016)
Background: Maternal high fructose (HF) intake induced renal programming and hypertension in male adult offspring. We examined whether maternal HF intake causes programmed hypertension and whether aliskiren administration confers protection against the process in a sex-specific manner, with a focus on the transcriptome changes in the kidney using next-generation RNA sequencing (NGS) technology and renin-angiotensin system (RAS). Methods: Pregnant Sprague–Dawley rats received regular chow or chow supplemented with 60% fructose throughout pregnancy and lactation. Offspring were assigned to six groups: male control, male HF (MHF), MHF+Aliskiren, female control, female HF (FHF), and FHF+Aliskiren. Oral aliskiren 10 mg/kg/day was administered via gastric gavage between 2–4 weeks of age. Rats were sacrificed at 12 weeks of age. Results: Maternal HF intake induced programmed hypertension in 12-week-old offspring of both sexes. HF regulated renal transcriptome and RAS components in the offspring kidney in a sex-specific manner. Aliskiren administration prevented HF-induced programmed hypertension in both sexes of adult offspring. Aliskiren administration increased ACE2 and MAS protein levels in female kidneys exposed to maternal HF intake. Conclusion: Maternal HF induced programmed hypertension in both sexes of adult offspring, which was sex-specifically mitigated by early aliskiren administration. Better understanding of the sex-dependent mechanisms that underlie maternal HF-induced renal programming will help develop a novel sex-specific strategy to prevent programmed hypertension.